Living with Spina Bifida : A Guide for Families and Professionals - Sandler, Adrian (Book collections on Project MUSE., 1997)
It is the most common complex birth defect. Spina bifida affects approximately one out of every 1,000 children born in the United States. In this [book, the author] offers ... useful information on the medical, developmental, and psychological aspects of this condition. [This book] is written especially for families and professionals who care for children, adolescents, and adults with spina bifida.-http://www.uncpress.unc.edu.